Necesidad de aplicar la suspensión condicional de la pena cuando se ha enervado la presunción de inocencia en segunda instancia - Rodríguez Gaona, Guicele Geoconda (2016)
With the purpose of analyzing and submitting a proposal for reform to our Organic Comprehensive Criminal Code regarding the Conditional Suspension of the Penalty, and its inapplicability in second instance, specifically in cases where innocence has been innervated in the Second Instance, that is, In cases where the defendant was first declared innocent, and in the second instance, the sentence is revoked and found guilty. It is therefore appropriate to analyze this issue in detail. With the above objective I have analyzed different aspects, the basis of this legal figure such as the Pena, its nature its justification, custodial sentences, non-custodial sentences, the origin and importance of the suspension Conditional sentence, as well as a brief analysis of the judgments or judicial decisions that exist in our jurisprudence. Observation of each of the constitutional principles which are being violated by the inapplicability of the conditional suspension in the second instance. Critical analysis on the figure of the conditional suspension of the sentence in both Ecuadorian legislation and in several legislations, such as the Spanish, Argentine and Dominican, among others; As the purpose of clarifying the form in which said procedure is typified.